Medical Management of Glaucoma - Barton, Keith; Hitchings, Roger A.; Budenz, Donald L.; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2013)
Medical Management of Glaucoma is a comprehensive review of glaucoma, current pharmacological therapies, and treatment guidelines for the disease as put forth by the American Academy of Ophthalmologists (AAO) and European Glaucoma Society (EGS). This book will review glaucoma$1 (Bs definition, classes, epidemiology, risk factors, pathogenesis (especially discussing intraocular pressure, aqueous humor production, and outflow), diagnosis and assessment tools, and current therapeutic options for patients. Medical Management of Glaucoma will also give ophthalmologists and related healthcare professionals insight into how the patient is affected by their disease by reviewing quality of life issues, adherence, and costs of therapy, which is particularly significant as the management of this chronic disease should be tailored for each patient.s
Author biographies -- Abbreviations -- Foreword -- Introduction -- Pathogenesis of glaucoma -- Diagnosing glaucoma -- Medical management of glaucoma.
Keywords: Medicine; Ophthalmology; Medicine & Public Health; Ophthalmology; Medicine/Public Health, general; Pharmacotherapy